COVID-19 Burden and Risk Among People With HIV. (1st June 2021) - Jones, Deborah L.; Morgan, Kristiana E.; Martinez, Paola C; Rodriguez, Violeta J.; Vazquez, Andres; Raccamarich, Patricia D.; Alcaide, Maria L.
Abstract : Background: This study evaluated COVID-19 risk and burden among people with HIV (PWH) in a US city with high rates of HIV and SARS-CoV-2 transmissions and examined the interrelationship between psychosocial factors and COVID-19 risk and burden. Setting: Participants were drawn from an existing consent to contact database of PWH. Database candidates were PWH, adults older than 18 years, people who had received HIV care at the University of Miami HIV clinics, people who spoke English or Spanish, and people who had agreed to be contacted for future research. Methods: An adapted version of the Multicenter AIDS Cohort Study/Women's Interagency HIV Study Combined Cohort Study COVID-19 survey was telephonically administered, requiring 15–30 minutes. Results: Psychological stress was a predictor of COVID-19 burden (financial and social burden) and COVID-19 risk (health factors associated with an increased risk of severe health outcomes due to infection with COVID-19). Having a history of traumatic events was associated with increased COVID-19 risk, and stress was associated with increased COVID-19 burden and COVID-19 risk. Conclusions: Overall, results suggest that the intersection of the HIV and COVID-19 pandemics may be most profound among those who have experienced traumatic events; and traumatic events may be associated with heightened vigilance regarding illness and infection.